2015
DOI: 10.1016/j.anifeedsci.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan affects total nutrient digestion and ruminal fermentation in Nellore steers

Abstract: a b s t r a c tThis study aimed to investigate the effects of chitosan on dry matter intake (DMI), nutrient digestibility, ruminal fermentation, and blood metabolites in Nellore steers. Eight ruminally cannulated Nellore steers (540 ± 28.5 kg of BW) were used in a replicated 4 × 4 Latin square design, with 21-d of experimental periods. The animals were randomly assigned to the following treatments: control (without chitosan addition; Q0), Q50, Q100 and Q150, by dosing 50, 100 and 150 mg/kg BW chitosan, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
54
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 14 publications
21
54
1
7
Order By: Relevance
“…The increase in plasma glucose concentrations in the current study is in agreement with the results reported by Araújo et al (2015) who also observed an increase in plasma glucose concentrations in Nellore steers. These results are consistent with the observed increase in the molar proportion of propionate and the propionate-to-acetate ratio in the rumen of sheep (Goiri et al, 2010) and Nellore steers fed chitosan (Araújo et al, 2015).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The increase in plasma glucose concentrations in the current study is in agreement with the results reported by Araújo et al (2015) who also observed an increase in plasma glucose concentrations in Nellore steers. These results are consistent with the observed increase in the molar proportion of propionate and the propionate-to-acetate ratio in the rumen of sheep (Goiri et al, 2010) and Nellore steers fed chitosan (Araújo et al, 2015).…”
supporting
confidence: 83%
“…These results are consistent with the observed increase in the molar proportion of propionate and the propionate-to-acetate ratio in the rumen of sheep (Goiri et al, 2010) and Nellore steers fed chitosan (Araújo et al, 2015). It is well established that other growth promoters, such as ionophores, increase ruminal propionate production and thereby increase the supply of this glucogenic substrate to the hepatic tissues, stimulating the production of glucose via gluconeogenesis (Sauer et al, 1989).…”
supporting
confidence: 79%
“…Although Araújo et al (2015) reported a linear increase in DM, NDF, and CP digestibility when evaluating the dose effect of chitosan on the digestion of Nellore steers, the authors did not report differences in DM intake. The authors suggested that those effects were related to altered ruminal fermentation, especially by increasing the propionate concentration.…”
Section: Discussionmentioning
confidence: 86%
“…However, the utilization of CHI in animal feeding has been underexploited, and there are few studies available in literature. Araújo et al (2015) reported a linear increase in the digestibility of DM, crude protein (CP), and neutral detergent fiber (NDF) when beef steers were fed CHI, without changing their DM intake.…”
Section: Introductionmentioning
confidence: 99%
“…Pode ser destacada também a diminuição de três das quatro relações avaliadas entre a concentração de AG que são produto e substrato da enzima estearoil-CoA dessaturase (SCD1) na glândula mamária para as vacas alimentadas com grão de soja nas dietas. Embora o exato mecanismo de ação da quitosana ainda não é conhecido, são observadas alterações no padrão de fermentação ruminal e aproveitamento de nutrientes (GOIRI et al, 2010a;ARAÚJO et al, 2015;, similar ao efeito dos ionóforos (IPHARRAGUERRE e CLARK, 2003; DUFFIELD et al, 2008). Assim como os ionóforos e a quitosana, os ácidos graxos, em especial AG insaturados, exercem efeito sobre o metabolismo ruminal, pois também têm a capacidade de selecionar populações microbianas (JENKINS, 1993; LOURENÇO et al, 2010).…”
unclassified